VD_FINDINFO Décision / 2015 / 926 vom 11. Dezember 2015 - VD Tribunal cantonal (2015)
NON-LIEU, ADMISSION DE LA DEMANDE, DROIT D'ÊTRE ENTENDU, MOTIVATION DE LA DÉCISION | 29 al. 2 Cst., 319 al. 1 CPP (CH), 393 al. 1 let. a CPP (CH), 393 al. 2 let. a CPP (CH)